Robust decentralized control for large-scale web-winding systems: A linear matrix inequality approach. (July 2017) - Hou, Hailiang; Nian, Xiaohong; Xu, Shaozhang; Sun, Miaoping; Xiong, Hongyun
In this paper, a robust decentralized control scheme is proposed for web-winding systems. The control input for each subsystem is divided into two parts, a reference control input and a control compensation. First, the reference control inputs and the error dynamic models are presented. Then, based on the error dynamic model, a decentralized controller is designed to compute the control compensation, and the relevant sufficient condition for the existence of the decentralized controller is derived in terms of linear matrix inequalities (LMIs). By virtue of regarding some parameters as interval variables, the proposed controller has good robustness with regard to parameter variations and is adapted to the changes of set point. Finally, a three-motor web-winding system is considered as an application example, and simulation and experimental tests illustrate the effectiveness of the proposed controller.